Innovative ways of student engagement for active learning in science courses of nursing in the four year baccalaureate program - Shehla Khan; Shagufta Iqbal (Journal of the Pakistan Medical Association, 2021)
Active learning strategies with innovative ways are now being used in the teaching and learning for the engagement of students in the classroom settings. A number of studies talks about the benefits the students have shown through their skills while using the active learning methods in their science courses that is Biochemistry, Anatomy and Physiology, Microbiology and Pathophysiology. It has been observed that active learning helps to retain material, motivate students and most of the time develops thinking skills.In the science courses of nurse education these are very much in use for developing the critical thinking qualities in their student nurses. Simply the nurse educator’s apply the process of active learning by engaging the students with the content. By applying active learning strategies in science courses of nursing education one could clearly see how the students get engaged with the content. Continuous....